2015
DOI: 10.1021/acsami.5b04201
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antifouling Properties of Carbohydrate Coated Poly(ether sulfone) Membranes

Abstract: Polyethersulfone membranes (PES) were modified with biologically active monosaccharides and disaccharides using aryldiazonium chemistry as a mild, one step, surface modification strategy. We previously proposed the modification of carbon, metals, and alloys with monosaccharides using the same method; herein we demonstrate modification of PES membranes and the effect of chemisorbed carbohydrate layers on their resistance to biofouling. Glycosylated PES surfaces were characterized using spectroscopic methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…Coupons of polyethersulfone (PES), stainless steel (SS316) and Nylon-6 (N6) were first modified using lactoside groups via spontaneous reaction of aryldiazonium cations to yield Work from our group demonstrated that PES undergoes functionalization by spontaneous reaction after immersion of pristine substrates in these solutions and we refer to our previous publication for a full characterization of Lac-PES surfaces thus obtained. 33 In the case of SS316 and N6, surfaces were pre-activated prior to functionalization. SS316 surfaces were pre-activated in caustic hypochlorite (bleach) solutions; this treatment is known to have cleaning and oxidising effects on SS316 surfaces.…”
Section: Aryldiazonium Modification Of Stainless Steel and Nylon Couponsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coupons of polyethersulfone (PES), stainless steel (SS316) and Nylon-6 (N6) were first modified using lactoside groups via spontaneous reaction of aryldiazonium cations to yield Work from our group demonstrated that PES undergoes functionalization by spontaneous reaction after immersion of pristine substrates in these solutions and we refer to our previous publication for a full characterization of Lac-PES surfaces thus obtained. 33 In the case of SS316 and N6, surfaces were pre-activated prior to functionalization. SS316 surfaces were pre-activated in caustic hypochlorite (bleach) solutions; this treatment is known to have cleaning and oxidising effects on SS316 surfaces.…”
Section: Aryldiazonium Modification Of Stainless Steel and Nylon Couponsmentioning
confidence: 99%
“…Carbohydrate layers prepared via aryldiazonium chemistry are molecular coatings in the 1-2 nm thickness range that preserve the topography of the original substrate, 31,33 so that their main effect is expected to be on surface chemistry and free energy. Results from field experiments show that in the absence of rinsing these coatings do not significantly impact on fouling resistance and little difference is observed with controls.…”
Section: Ss Pre-treatedmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to mimic biological antifouling strategies, work has focused on the use of immobilized carbohydrates, given the presence of these molecules in the antiadhesive glycocalyx that surrounds certain cells 18 19 . Research shows, in fact, that oligo- and polysaccharide coatings can control fouling and protein adsorption, while being extremely stable to oxidation 20 21 22 23 24 25 26 .…”
mentioning
confidence: 99%
“…These coatings are environmentally benign and highly stable as compared to other chemical species. Additionally, these carbohydrate coatings were fabricated on poly (ether sulfone) (PES), which demonstrates lower fouling in a complex aqueous environments that are rich in biomass such as the wastewater effluent, as compared to the bare PES membrane surfaces [92]. Subsequently, the performance of carbohydrates immobilized fouling resistant coatings in the marine environment were studied on three different substrates: stainless steel, nylon and PES.…”
Section: Surface Chemistrymentioning
confidence: 99%